2004
DOI: 10.1364/opex.12.000941
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion properties of square-lattice photonic crystal fibers

Abstract: In this paper the guiding properties of photonic crystal fibers with a square lattice of air-holes in a silica matrix have been studied for the first time. The dispersion curves of fibers with different hole-to-hole spacing and air-hole diameter have been accurately calculated. Negative values of the dispersion parameter and the dispersion slope have been obtained with a hole-to-hole spacing of 1 microm. A comparison between fibers with square and triangular lattice has been also performed, taking into account… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(63 citation statements)
references
References 1 publication
3
60
0
Order By: Relevance
“…Most of the air holes in the PCFs cladding have been arranged either in a periodic triangular or periodic square orientation. The modal properties, in particular, and the dispersion properties of the above types of PCFs can be altered by varying the hole-to-hole spacing (Λ) and the air hole diameter ( ) with air-filling fraction being /Λ [3,4]. Both types of PCFs with a silica background can be successfully implemented to compensate the positive dispersion parameter and dispersion slope of the existing inline fibers [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the air holes in the PCFs cladding have been arranged either in a periodic triangular or periodic square orientation. The modal properties, in particular, and the dispersion properties of the above types of PCFs can be altered by varying the hole-to-hole spacing (Λ) and the air hole diameter ( ) with air-filling fraction being /Λ [3,4]. Both types of PCFs with a silica background can be successfully implemented to compensate the positive dispersion parameter and dispersion slope of the existing inline fibers [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, their dispersion and dispersion tolerance varies uniquely. Figure 3a shows the fiber cross-section of a four-ring S-PCF (Bouk et al 2004) with the air-hole to air-holes spacing, or pitch K, and the diameter d of the air-holes. The first ring comprises eight air-holes; the second ring comprises 16 air-holes, and so on.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…The core is formed by omitting a single air-hole from the center (Figure 3a). Bouk et al (2004) has reported positional change of the air-holes for the square PCF and the hexagonal PCF. Figure 3b shows the chromatic dispersion characteristics of the S-PCF as a function of wavelength.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…2, the second in the center of the red squares (inverse Thue-Morse fiber). Note that the cladding of these PQFs can be considered as a rectangular arrangement of air holes in silica [26] where some of them have been removed according to the Thue-Morse rules. The core of the fibers is performed by reducing the size of the central holes in the direct fiber or by introducing an extra central hole in the inverse fiber.…”
Section: Design Of the Thue-morse Based Pqfmentioning
confidence: 99%